Dose-dependent cytotoxicity of clinically relevant cobalt nanoparticles and ions on macrophages in vitro. - Kwon, Y; Xia, Z; Glyn-Jones, S; Beard, D; Gill, H; Murray, D (Institute of Physics Publishing, 2009)
Despite the satisfactory short-term implant survivorship of metal-on-metal hip resurfacing arthroplasty, periprosthetic soft-tissue masses such as pseudotumours are being increasingly reported. Cytotoxic effects of cobalt or chromium have been suggested to play a role in its aetiology. The aim of this study was to investigate the effects of clinically relevant metal nanoparticles and ions on the viability of macrophages in vitro. A RAW 264.7 murine macrophage cell line was cultured in the presence of either: (1) cobalt, chromium and titanium nanoparticles sized 30-35 nm; or (2) cobalt sulphate and chromium chloride. Two methods were used to quantify cell viability: Alamar Blue assay and Live/Dead assay. The cytotoxicity was observed only with cobalt. Cobalt nanoparticles and ions demonstrated dose-dependent cytotoxic effects on macrophages in vitro: the cytotoxic concentrations of nanoparticles and ions were 1 x 10(12) particles ml(-1) and 1000 microM, respectively. The high concentration of cobalt nanoparticles required for cytotoxicity of macrophages in vitro suggests that increased production of cobalt nanoparticles in vivo, due to excessive MoM implant wear, may lead to local adverse biological effects. Therefore, cytotoxicity of high concentrations of metal nanoparticles phagocytosed by macrophages located in the periprosthetic tissues may be an important factor in pathogenesis of pseudotumours.